Correction of prediction model output for structural design and risk-based inspection and maintenance planning. (15th March 2015) - Hifi, Nabile; Barltrop, Nigel
Abstract: This paper presents a new methodology to calibrate structural reliability models output. The methodology combines data from experience and prediction models to correct the structural reliability models. The paper gives an overview of the techniques used for model calibrations, summarises the methodology in an overall discussion, and proposes data processing to sanitise sensitive information. The proposed methodology is inherently adaptable and can be applied to many other fields that require cost effective maintenance, as well as providing data for calibrating methods and codes. Highlights: Newly developed methodology to calibrate prediction models of structural defects and degradations. Use of the methodology at the design stage and for inspection planning as a decision support system tool. Improve the ship structural performance and make inspections cost-effective. Use of expert opinion in conjunction with data from inspection to correct the structural reliability models.